Action research in healthcare - Koshy, Elizabeth. 4 0 16; (Heather) 1945- Waterman, H.;Koshy, Valsa; 5 (Los Angeles : SAGE, 2011)
This is a practical guide to using research for improving practice in healthcare contexts. Taking you through the process step-by-step, the book explains how to tackle each stage of your project - from planning the study and undertaking a literature review, through to gathering and interpreting data and implementing findings.
What is action research? -- Engaging in action research -- Reviewing literature -- Steps in the action research process: practical considerations -- Gathering data -- Analysis data and generating evidence -- Writing up and publishinh action research.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Methods.;Methods. -- Action research in public health.;Health services research;Data collection;Quality improvement.;Research design. -- 20; 20; 2